Acid activation of bleaching earth for crude palm oil treatment / Farihahusnah Hussin - Farihahusnah, Hussin (2013)
The unique properties of clay and clay minerals caused them to be valuable in a wide range of industrial applications. Low cost, availability and effectiveness are the prevailing factors that promoted clay and clay minerals to be used extensively as adsorbents in the purification of vegetable oils. The main objective of this study is to produce new types of activated clay by hydrofluoric acid activation and modify the surface physical of hydrofluoric acid activated clays in order to enhance their bleaching performance. Experiments were divided into two parts. In part 1, montmorillonite clay was activated with hydrofluoric acid (HF) and sulphuric acid (H2SO4) at 90oC using a range of activation times of 1, 3, 5, and 7 hours, and at various acid concentrations of 2, 3, 4, 5, and 6 M. The structure and surface texture of the prepared materials were characterised by X-ray fluorescence spectrometer (XRF), X-ray diffraction (XRD), Fourier Transmittance Infrared (FTIR), BET surface area and Scanning electron microscope (SEM). Results indicated that increasing the acid concentration and activation time, increases the dissolving rate of octahedral cations (Mg, Fe and Al). They also showed that the clay activated with HF has the highest dissolution, followed by H2SO4 activated clay and then the natural clay sample. Therefore, activation with sulphuric and hydrofluoric acid caused structural changes in the activated clay samples. In addition, the specific surface areas in the acid activated clays are larger than the natural clay. The specific surface areas in acid activated clays also increase several times as the acid concentration and activation time increases. In part 2, a study was carried out with the intention to assess and compare the bleaching performance of the acid activated clay with that of the natural clay and commercial activated clay, and also to investigate the effect of the activation parameters, namely acid concentration and activation time. The effects of acid concentration and activation time on the bleaching iv performance were evaluated by determining the percentage (%) of Lovibond red colour index. Results revealed that, for the same amount of bleaching clay, the percentage removal of free fatty acids, red colour index, peroxide value and phosphorus content appeared higher in the sample that activated with H2SO4 and HF. On the other hand, the clay activated with HF gave the best results in terms of retaining the original carotene content of the oil. The results showed that, HF activated clay has almost similar carotene content as the original crude palm oil. This might imply that HF activated clay is a good candidate to be used as an adsorbent in the purification of palm oil. Nevertheless, it was shown that the clays activated with 5 M H2SO4 and 3 M HF at 1 hour activation time were appropriate adsorbents for the purification of palm oil. At these conditions, these clays produced oils with the least free fatty acid and peroxide value as well as with the best red colour index removal.